2020
DOI: 10.1097/brs.0000000000003367
|View full text |Cite
|
Sign up to set email alerts
|

Black Race as a Social Determinant of Health and Outcomes After Lumbar Spinal Fusion Surgery

Abstract: Study Design. A retrospective analysis of patient hospitalization and discharge records. Objective. To examine the association between race and inpatient postoperative complications following lumbar spinal fusion surgery. Summary of Background Data. Racial disparities in healthcare have been demonstrated across a range of surgical procedures. Previous research has identified race as a social determinant of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…To date, studies evaluating a potential role of these disparities among patients undergoing single-level lumbar fusions have solely focused upon race/ethnicity, household income, and insurance and have not elucidated the impact of other SDH. [9][10][11] To this end, the present study explores the potential impact of SDH on specific postoperative outcomes among patients undergoing single-level lumbar fusions.…”
mentioning
confidence: 99%
“…To date, studies evaluating a potential role of these disparities among patients undergoing single-level lumbar fusions have solely focused upon race/ethnicity, household income, and insurance and have not elucidated the impact of other SDH. [9][10][11] To this end, the present study explores the potential impact of SDH on specific postoperative outcomes among patients undergoing single-level lumbar fusions.…”
mentioning
confidence: 99%
“…Minority patients have been reported to have longer post-operative hospital stays when compared to their White counterparts [ 3 , [7] , [8] , [9] ]. A recent retrospective cohort study, by Reyes et al ., evaluated national discharge data of over 149,000 patients who underwent a lumbar spinal fusion in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Minority patients have been reported to have longer post-operative hospital stays when compared to their White counterparts. [3], [7]- [9] A recent retrospective cohort study, by Reyes et al, evaluated national discharge data of over 149,000 patients who underwent a lumbar spinal fusion in 2016. The authors reported that Black and Hispanic patients had longer LOS and higher rates of prolonged LOS than White patients who underwent the same procedure.…”
Section: Length Of Stay (Los)mentioning
confidence: 99%
See 2 more Smart Citations